Getting Social: The Use of Social Media to Improve Alumni Response Rates for Assessment of Program Outcomes. Issue 6 (November 2017) - Fiorentino, Lisa; Haley, Tammy
Abstract : Abstract: Outcome assessment has become standard in institutions of higher learning and is a requirement of State Boards of Nursing and major accrediting bodies, including all accrediting agencies for programs in nursing. Appropriate identification of student learning outcomes and program outcomes to ensure the collection of relevant and meaningful data is essential. Although much has been written about what should be included in assessment, little information exists on how to best collect the required data for evaluation. This article describes an innovative approach to improving alumni response rates to assess program outcomes through the use of social media.